Новий збірник наукових праць про українців Холмщини і Підляшшя - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (Волинський національний університет імені Лесі Українки, 2008)
Рецензовано збірник наукових праць "Українці Холмщини і Підляшшя: історична доля, духовна і матеріальна культура впродовж віків". Проаналізовано рівень висвітлення проблем, на які звертають увагу його автори. Виокремлено важливість фотоматеріалів у збірці.

The collection of scientific works "Ukrainians of the Kholmshchyna and Pidlyashshya: historical fate, spiritual and material culture for centuries" was reviewed. The level of coverage of problems, which are drawn attention by its authors, is analyzed. The importance of photo materials in the collection is highlighted.
A new collection of scientific works on Ukrainians of the Kholmshchyna and Pidlyashshya
Keywords: українці; Холмщина; Підляшшя; збірник наукових праць; рецензія; Ukrainians; Kholmshchina; Pidlyashshya; collection of scientific works; review